Sanksi Pidana Bagi Pelaku Kekerasan Pencabulan Terhadap Anak Menurut UU No. 23 Tahun 2002 dan Hukum Islam (Studi Putusan PN Bengkulu No. 185/PID.B/2013/PN.BKL) - Semboda, Arip (UIN Fatmawati Sukarno Bengkulu, 2016)
Criminal Sanctions for Violator of Sexual Abuse Against Children by Act no. 23 years 2002 and Islamic law (Study of Bengkulu Court Decision no. 185 / pid.b / 2013 / PN.BKL). This study analyzes the Bengkulu District Court judge’s decision in a criminal case of sexual abuse against children Number: No. 185 / Pid.B / 2013 / PN.Bkl terms of the Act. 23 of 2002 and the law of Islam. Using qualitative research methods, types of legal normative juridical, with the approach of legislation, case approach and conceptual approach through the study of literature and documentary studies. The results showed that the execution of criminal sanctions against the perpetrators of sexual abuse of children, according to Law. 23 of 2002 as amended by Law No. 35 of 2014 on the protection of children can be carried out by a panel of judges to apply Article 82, if the defendant proved to meet the elements of objective and subjective elements, while the implementation of Islamic law can be applied ta’zir criminal sanction, namely the legal sanctions established by judges / legal government, Then the decision handed down by the judges on the Bengkulu District Court case number: 185 / Pid.B / 2012 / PN.Bkl, has been proven legally and convincingly guilty of committing the crime of sexual abuse of children as stated in Article 82 of Law No. 23 of 2002 to convict four years in prison and a fine of 60,000,000, - (sixty million rupiahs), while in Islamic law, perpetrators of abuse may be subjected to caning (jild) or more can create a deterrent effect and the pain is not too long with the purpose of providing education/ teaching (ta’dib) and prevention (zajr).